Land Consolidation Policy in Addressing Slums and Tidal Flooding: A Case Study of Kampung Bugisan - Widura, Elsa; Dewi , Asih Retno; Hapsari , Wijayanti (The Journal of Indonesia Sustainable Development Planning, 2025)
Tidal flooding has significantly impacted the settlements in Kampung Bugisan, requiring a collaborative approach for resolution. This study aims to describe the challenges and key elements of land consolidation that have alleviated slum conditions and contributed to sustainable development. A qualitative descriptive method used primary data from interviews and direct observations, which was combined with secondary data from reports, spatial documents, and publications. These data were validated through triangulation. The findings reveal challenges in implementing land consolidation in Kampung Bugisan, including its prolonged duration, low community awareness, and land administration issues. Although a top-down approach in site selection, land consolidation was successful due to the environmental pressures and the community’s inability to overcome the problems. Participatory and inclusive elements must involve local leaders to strengthen the community's trust. The successful implementation depends on collaboration, community participation, and comprehensive development, therefore contributing to SDGs 6, 9, 11, 16, and 17 for sustainability.